The importance of intership in Kolej Yayasan Pelajaran Johor towards culinary art students - Md Sahak, Adibah Aishah; Mohd Reza, Sakeenah; Md Yunus, Melor (Malaysian Journal of Social Sciences and Humanities (MJSSH), 2017)
The higher learning institution especially private college is growing day by day with the variation of course especially for the culinary art students. Culinary Arts is one area in Technical Vocational Education and Training (TVET) where students need to adapt the real-world working as a chef besides fundamental subject matter knowledge, techniques and hands-on skills for cooking in order to survive in the industry. The course syllabus of culinary art is patterned to provide a stage for students who want to be a chef in the future. This study is looking forward to find the importance of internship in Kolej Yayasan Pelajaran Johor towards culinary art students. The internship is gradually enhancing the student knowledge, confidence level and performance which enable them to be more confident when coming back from internship. This positive indication and feedback may affect towards students, lecturers, private institutional itself and Ministry of Higher Education.